Anxiety and Sleep Problems of College Students During the Outbreak of COVID-19 - Wang, Xing; Chen, Hongguang; Liu, Ling; Liu, Yuan; Zhang, Nan; Sun, Zhenghai; Lou, Qing; Ge, Weichun; Hu, Bo; Li, Mengqian (Frontiers in Psychiatry, 2020)
This study aimed to explore the psychological status and its influencing factors of college students during the outbreak of COVID-19. An online questionnaire survey was conducted among 3,092 Chinese college students who were quarantined at home due to the COVID-19 outbreak. The survey tools included the Generalized Anxiety Disorder 7-Item Scale (GAD-7), the Perceived Stress Scale (PSS-10), and the Self-Rating Scale of Sleep (SRSS). Of all the respondents, the prevalence of anxiety symptoms, sleep problems, any of the two, and both of the two were 16.8%, 13.5%, 25.1%, and 5.3% respectively. 43.7% of college students with higher perceived stress. Factors associated with anxiety symptoms included higher frequency of daily news reading (1-3 times; 4-7 times; more than 7 times), having sleep problems, higher stress and careless the number of remaining masks; factors associated with sleep problems include postgraduates, the frequency of daily news reading (1-3 times), the frequency of going out per week (1-3 times), having anxiety symptoms and higher stress; factors associated with higher perceived stress included higher frequency of daily news reading (4-7 times), remaining masks (1-10; more than 20), having anxiety symptoms and having sleep problems. The prevalence of anxiety symptoms, sleep problems and higher perceived stress among investigated college students were high during the COVID-19 outbreak. Particular attention should be paid to the psychological problems of college students quarantined at home, especially for those at high risk for psychological problems.